Determination of selenium by GFAAS in slurries of fish feces to estimate the bioavailability of this micronutrient in feed used in pisciculture - Silva, Fabio A.; Neves, Renato C. F.; Quintero-Pinto, Luis G.; Padilha, Cilene C. F.; Jorge, Sonia M. A.; Barros, Margarida Maria [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Elsevier B.V., 2007)
This paper presents a simple, fast and sensitive method to determine selenium in samples of feces and of fish feed by graphite furnace atomic absorption spectrometry (GFAAS) through the direct introduction of slurries of the samples into the spectrometer's graphite tube. The limits of detection (LOD) and quantification (LOQ calculated for 20 readings of the blank of the standard slurries (0.50% m/v of feces or feed devoid of selenium) were 0.31 mu g 1(-1) and 1.03 mu g 1(-1), respectively, for the standard feces slurries and 0.35 mu g 1(-1) and 1.16 mu g 1(-1), respectively, for the standard feed slurries. The proposed method was applied in studies of bioavailability of selenium in different fish feeds and the results proved consistent with that obtained from samples mineralized by acid digestion using the microwave oven. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: bioavailability of selenium in fish feed; selenium in fish feces; determination of selenium by GFAAS; toxic limit of selenium in pisciculture